MIGRATION TRENDS IN KAZAKHSTAN RELATED TO GEOPOLITICAL SITUATIONS (ҚазҰУ Хабаршысы. География сериясы, 2025)
Modern migration goes beyond natural movement, national demographic policy and is linked to national security. Firstly, in the context of globalization, the world is in a state of constant migration. The degree of influence of migration on the socio-economic, political and demographic situation in various countries has increased, never before has the migration factor played such an important role in the aspect of ensuring national security and on this basis the conflict of interests of states, including allies and integration partners. At the same time, the Republic of Kazakhstan is actively involved in modern international migration, which is a search for effective means of managing migration for the benefit of society and the State. An important factor in the formation of channels of illegal migration of foreign citizens in transit through Kazakhstan is the unstable socio-political and domestic economic situation in neighboring countries, the war in Russia and Ukraine, events in Afghanistan and the Middle East, as well as the consequences of periodic armed conflicts in the Central Asian region. The West Kazakhstan border region of Kazakhstan is a region with active population migration and is considered as a key region of the republic.  Thus, the relevance of making a forecast and action plan for future flows was determined by an in-depth study of migration trends from this aspect and identification of cause-and-effect relationships